The purpose of philosophy and the criterion of truth in wittgenstein's tractatus logico-philosophicus - Carrera-Honores, Luis (2021)
The objective of this research is to explain the purpose of the philosophy and the criterion of truth that underlies the Tractatus logico-philosophicus. In this text, Wittgenstein developed the following ideas: First, the starting point for Wittgenstein is the world. Second, the world is what is the case and what is the case are the facts. Third, facts are expressed in thought because thought is the logical figure of events. Fourth, thought is a logical proposition of the world. Fifth, the proposition is a truthful function and this truthful function is the form of the proposition. Finally, the form of the proposition gives the logical limits to language and this limit is the limit of what can be spoken and what can not be spoken should be unvoiced. Therefore, in the Tractatus the purpose of philosophy is clearly and explicitly demarcate the limits of the world, to solve and get out of the various confusions that exist in Western philosophy since its beginning, and the logical language has the purpose of establishing the correspondence between the logical proposition and the atomic fact.